Stable Pyrrole‐Linked Bioconjugates through Tetrazine‐Triggered Azanorbornadiene Fragmentation. Issue 15 (18th February 2020) - Gil de Montes, Enrique; Istrate, Alena; Navo, Claudio D.; Jiménez‐Moreno, Ester; Hoyt, Emily A.; Corzana, Francisco; Robina, Inmaculada; Jiménez‐Osés, Gonzalo; Moreno‐Vargas, Antonio J.; Bernardes, Gonçalo J. L.
Abstract: An azanorbornadiene bromovinyl sulfone reagent for cysteine‐selective bioconjugation has been developed. Subsequent reaction with dipyridyl tetrazine leads to bond cleavage and formation of a pyrrole‐linked conjugate. The latter involves ligation of the tetrazine to the azanorbornadiene‐tagged protein through inverse electron demand Diels–Alder cycloaddition with subsequent double retro‐Diels–Alder reactions to form a stable pyrrole linkage. The sequence of site‐selective bioconjugation followed by bioorthogonal bond cleavage was efficiently employed for the labelling of three different proteins. This method benefits from easy preparation of these reagents, selectivity for cysteine, and stability after reaction with a commercial tetrazine, which has potential for the routine preparation of protein conjugates for chemical biology studies. Abstract : Click to stabilize : An azanorbornadiene bromovinyl sulfone reagent allows site‐selective protein modification and, in combination with a tetrazine partner, enables the preparation of stable pyrrole‐linked protein conjugates through a new bond‐cleavage reaction. The latter proceeds through a three‐step cascade reaction involving an inverse electron demand Diels–Alder (iEDDA) cycloaddition between tetrazine and the azanorbornadiene‐tagged protein, and two subsequent retro‐Diels–Alder ( r DA) reactions.